Perkembangan Cerai Gugat Di Kota Padang (Studi Kasus Pengadilan Agama Padang 2015-2022) - Maisarah Sheilla; Najmi Najmi (Jurusan Sejarah FIS UNP, 2023)
ABSTRACK This research discusses the phenomenon of contested divorce in Padang City (2015-2022). The purpose of this study is to describe the study of women's studies from the perspective of divorce in the city of Padang, and the factors that influence the reasons for the increase in divorce actions in the Religious Courts of the city of Padang. The research method used consists of (1) heuristics, 2) source criticism, 3) interpretation, 4) historigraphy. The research findings show data from the Padang Religious Court that divorce claims continue to dominate more than talak divorces, in 2015 the number of lawsuits received exceeded the number of lawsuits that occurred in the previous year. In the following year, this continued to exceed the number of divorce claims received at the Religious Court in Padang City. Women who file for divorce in the city of Padang are more nuanced in their profession as housewives. The results of the research on the factors that influence divorce continue to dominate in the city of Padang, namely infidelity, women are not supported, women feel oppressed in the household (domestic violence), are victims of polygamy, there are economic factors, and frequent conflicts occur. Keywords: Divorce Lawsuit, Women, Factors causing ABSTRAK Penelitian ini membahas tentang fenomena cerai gugat di Kota Padang (2015-2022). Tujuan penelitian ini untuk mendeskripsikan kajian sejarah perempuan dari perspektif cerai gugat di Kota Padang, dan faktor yang mempengaruhi alasan meningkatnya gugatan cerai di Pengadilan Agama Kota Padang. Metode penelitian yang digunakan terdiri dari (1) heuristic, 2) kritik sumber, 3) interpretasi, 4 ) historigrafi. Temuan penelitian menunjukkan data yang berasal dari Pengadilan Agama Padang bahwasannya cerai gugat terus mendominasi lebih banyak dibandingkan cerai talak, tahun 2015 angka cerai gugat yang diterima melebihi angka cerai gugat yang terjadi pada tahun sebelumnya. Hal demikian ditahun berikutnya terus melebihi angka cerai gugat yang diterima pada Pengadilan Agama di Kota Padang. Perempuan yang mengajukan gugatan cerai di Kota Padang lebih didominasi berprofesi sebagai Ibu RT. Hasil penelitian faktor-faktor yang mempengaruhi cerai gugat terus mendominasi di Kota Padang adalah perselingkuhan, perempuan tidak dinafkahi, perempuan merasa tertindas dalam berumah tangga (KDRT), menjadi korban poligami, adanya faktor ekonomi, serta sering terjadi perselisihan. Kata Kunci : Cerai Gugat, Perempuan, Faktor Penyebab